PSYCHOLOGICAL PECULIARITIES OF THE EXISTENTIAL DEATH ANXIETY IN THE ADOLESCENTS - Shulha, Halyna; Chukhrii, Kateryna (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to the issue of the psychological peculiarities of the existential death anxiety in the adolescents. Based on the analysis, generalization and systematization of the different scientific works and previous researches, the importance of avoiding the impact of the negative factors on the personality of the teenagers for their proper living and decreasing the probability of the emergence and further development of the existential death anxiety was substantiated. The peculiarities of the existential death anxiety in the adolescent age and the factors that can be the ground for its formation are found out. The main results of the empirical research of the psychological peculiarities of the existential death anxiety in the adolescent age are theoretically substantiated and revealed (n=67). For the diagnosis of the thanatic anxiety level and thanatic feelings «Templer’s Death Anxiety Scale» was used. Having considered the peculiarities of death anxiety in the adolescents, we revealed the factors that, in our opinion, have the significant impact on its formation. It would therefore be useful to study and analyze these factors. Among such we singled out anxiety which we studied by D. Maudsley’s self-esteem anxiety, rigidity and extraversion method; peculiarities of realization of the different time perspectives which were studied by means of Ph. Zimbardo’s time perspective inventory test; attitude to life, death and critical situation which were examined by A. Bakanova’s method. The results of the quantitative and qualitative analysis of the empirical data made it possible to summarize regarding the direct correlation between the scales of the thanatic feelings and anxiety, the thanatic feelings and negative past, the thanatic anxiety and hedonic present in the lads and the direct correlation between the scales of extraversion and the thanatic feelings, the thanatic feelings and negative past in girls. There was also revealed the reverse correlation between the scales of rigidity and the thanatic feelings, the thanatic anxiety and positive past in lads, the thanatic anxiety and future in girls. There was determined a perspective of the further scientific works on the issue of the research, namely the research of the general psychological state of the lads, the determination of their life priorities and values, the research of the emotional states of the lads, the determination of the impact of the psychological processes and properties on the formation of the existential death anxiety in the adolescents, the development the recommendations on the prevention of the death anxiety formation and also the correction of the high level of the death anxiety development in the lads etc.